Review on South Korea-United States Trade Relations: The Significance of America First’s Doctrine - Demeiati Nur Kusumaningrum; Septian Nur Yekti (President University, 2020)
AbstractThe United States under President Donald Trump administration is marked by several government policies aimed at returning US leadership to the world political arena in both the economic and security fields. He argues that economic policy through the doctrine of America First will save income and create jobs for Americans and will help restructure the US economy. This paper describes the impact of America First's doctrine on US trade relations with South Korea. Refering to the history of US trade relations, the free market system has become a priority in international negotiations, both through bilateral and multilateral agreements. It examines South Korea has come out of the spirit of free trade agreed by the two countries. Since the implementation of Korus FTA until 2017, South Korea has adopted a policy pattern that initially did not comply with the poin of agreement. In March 2016, the senate head of the financial commission sent a letter to the South Korean ambassador discussing the implementation of commitments to data flow, transparency and predictability of pricing and reimbursement of pharmaceutical products and medical devices, and the possibility of US companies investing and operating with companies South Korea. The proposal for renegotiation was approved by South Korea in October 2017, which agreed to hold discussions for modification and amendment and fulfill the necessary domestic procedures in December 2017.Keywords: America First Doctrine, Foreign Policy, Korea, Negotiation, Trade